The University of Athens Hellenic Macroseismic Database (HMDB.UoA): historical earthquakes - Kouskouna, Vicki; Sakkas, George (2013)
A systematic study of historical earthquakes leading to the quantification of earthquake effects in terms of macroseismic data points (MDPs) and, consequently, earthquake parameters has been carried out in the last decade at the Laboratory of Seismology of the University of Athens. For each earthquake, the available background information was evaluated and the corresponding macroseismic intensities assessed in terms of the European Macroseismic Scale 1998. A considerable amount of these MDPs contributed to the Archive of Historical Earthquake Data inventory through European initiatives (NERIES and SHARE). Based on the structure of the European Database, the local version of the Hellenic Macroseismic Database (HMDB.UoA) was designed incorporating historical earthquakes of the period 1000–1899 from the eastern Aegean area, central Greece and Ionian Islands. In its present form, the HMDB.UoA includes 90 events with Imax ≥ 7 (868 MDPs) and 1,088 events with Imax < 7 (1,273 MDPs). The database is hosted on the website http://macroseismology.geol.uoa.gr/.